Zakat Perdagangan bagi Muḥtakir Menurut Perspektif Mazhab Māliki - Nurul Istiqamah; Rosmita Rosmita (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2023)
This study aims to find out and understand the opinion of the Imam Mālik school regarding trade zakat for muḥtakir. The type of research used is library research, namely research with the object of data review in the form of library texts, which is descriptive qualitative in nature, namely describing data obtained from various sources which are then analyzed to obtain conclusions, using a juridical approach. normative and philosophical. The results of the study are as follows: first, trade zakat is anything that is prepared to be traded which when it reaches the haul and nisab of trade zakat it is obligatory to issue zakat and ihtikar is the hoarding of merchandise so that its circulation in society becomes reduced and then when people need it later get it out at a higher price. Second, the opinion of the Imam Mālik school regarding the timing of issuing trade zakat for the muḥtakir, namely if he has sold his merchandise after one year or after several years, the muḥtakir is obligated to issue his zakat with the calculation for one year. Imam Mālik's opinion is based on kias mursal, namely a kias that is not based on a source of law that has been determined by the shari'a, but is based on the benefit that is in accordance with the shari'a.